2005
DOI: 10.1001/archneur.62.10.1595
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neurotoxicity in Primary Central Nervous System Lymphoma

Abstract: Background: Treatment for primary central nervous lymphoma (PCNSL) with chemotherapy and radiotherapy has resulted in improved survival, but some patients develop neurologic deterioration that represents a treatment-related toxic effect. This delayed neurotoxicity has been poorly defined in the literature, and the underlying mechanisms are unknown. Objective: To describe the clinical findings, time course, and pathophysiologic mechanisms associated with neurotoxicity in an attempt to generate hypotheses for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(136 citation statements)
references
References 33 publications
(20 reference statements)
6
128
1
1
Order By: Relevance
“…Omuro et al (4) reported that age ≥60 years was a statistically significant risk factor for developing neurotoxicity. Kiewe et al (19) evaluated surviving patients without evidence of lymphoma or late neurotoxicity, and reported a positive correlation between radiological and clinical abnormalities.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Omuro et al (4) reported that age ≥60 years was a statistically significant risk factor for developing neurotoxicity. Kiewe et al (19) evaluated surviving patients without evidence of lymphoma or late neurotoxicity, and reported a positive correlation between radiological and clinical abnormalities.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…However, leukoencephalopathy is associated with a risk of neurotoxicity and may severely interfere with cognitive function (2,3). Progressive leukoencephalopathy with cognitive deterioration is associated with a significant decrease in the quality of life (QOL) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Some 50% of long-term survivors develop latedelayed cognitive deficits due to radiation-induced injury of normal brain tissue (1,2). Age is an important risk factor for the development and severity of cognitive dysfunction following WBI, with pediatric and elderly patients appearing to be more vulnerable to WBI-induced brain injury than young adults (3)(4)(5)(6). There is a paucity of experimental data regarding the effects of old age on the radiation response in the brain despite evidence that the average age for developing the cancers that require treatment with WBI is > 50 years old, making middle-aged and older adults a commonly treated patient population (7).…”
Section: Introductionmentioning
confidence: 99%
“…Their confirmation of some long-term survivors emphasizes the need to consider the potential longterm neurotoxicity of treatment, as has become widely recognized in immunocompetent patients with primary central nervous system lymphoma. 3,4 …”
mentioning
confidence: 99%